2014
DOI: 10.7314/apjcp.2014.15.16.6649
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate Increases Radiosensitivity in Head and Neck Squamous Cell Carcinoma via Inducing G2/M Arrest and Apoptosis

Abstract: Radiation therapy is an important treatment for head and neck squamous cell carcinoma (HNSCC). However, how to promote radiation sensitivity in HNSCC remains a challenge. This study aimed to investigate the radiosensitizing effects of fenofibrate on HNSCC and explore the underlying mechanisms. HNSCC cell lines CNE-2 and KB were subjected to ionizing radiation (IR), in the presence or absence of fenofibrate treatment. Cell growth and survival, apoptosis and cell cycle were evaluated. In addition, CNE-2 cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
10
1
Order By: Relevance
“…A large number of studies have found that cell cycle regulation has a significant impact on the survival of tumor cells and their sensitivity to radiotherapy, where G2/M phase arrest can enhance the sensitivity of tumor cells to radiotherapy (17)(18)(19). The present study found that after radiotherapy, the G2/M phase ratio of HSC-4 cells in the experimental group was not significantly different compared with that in the control groups.…”
Section: Discussioncontrasting
confidence: 53%
“…A large number of studies have found that cell cycle regulation has a significant impact on the survival of tumor cells and their sensitivity to radiotherapy, where G2/M phase arrest can enhance the sensitivity of tumor cells to radiotherapy (17)(18)(19). The present study found that after radiotherapy, the G2/M phase ratio of HSC-4 cells in the experimental group was not significantly different compared with that in the control groups.…”
Section: Discussioncontrasting
confidence: 53%
“…The induction of cell cycle arrest at the G2/M phase in tumor cells may be an effective strategy for enhancing the ionizing radiation effect against tumors [28]. Numerous recent studies have shown that increasing radiation-induced G2/M phase arrest in tumor cells can significantly increase the sensitivity of HNSCC, cervical cancer, and prostate cancer cells to ionizing radiation[29][30][31][32]. In the present study, the cell cycle detection results after irradiation showed that the proportion of cells in the G2/M phase in the CNE-2sh group was significantly higher than that in the control group cells, indicating that FANCD2 silencing significantly increased radiation-induced G2/M phase cell cycle arrest in the CNE-2 cells and enhanced their ionizing radiation sensitivity.Interestingly, in ionizing radiation sensitivity experiments involving bone marrow stromal cells and IL-3-dependent hematopoietic stem cells of FANCD2-deficient mice, Berhane et al found that the growth life of bone marrow stromal cells was shortened and showed strong radiation sensitivity and DNA damage involvement.…”
mentioning
confidence: 99%
“…For example, fenofibrate inhibited G 1 /S phase progression in endometrial cancer by down-regulation of Cyclin D1 (CCND1) 23 , and in glioblastoma cells by activation of FoxO3A/Bim apoptotic axis 25 . In head and neck squamous cell carcinoma, fenofibrate leaded to G 2 /M arrest via reducing the activity of the CDK1/cyclinB1 kinase complex 26 . To elucidate the anti-tumor mechanism of bezafibrate, we virtual screened out some bezafibrate-binding candidate proteins by TarFisDock (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%